Interpreting Neologisms Used in Korea’s Rapidly Changing Society: Delivering the Meaning of Neologisms in Simultaneous Interpretation - Choi, Jungwha (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractThis study will review what kind of neologisms have appeared between the period of 2003-2004, categorize them, and examine how they have been interpreted in order to faithfully convey what the speaker's intent is, that is the vouloir-dire. The presentation will cover the following points:reasons for the formation of neologisms; their impact on TL expression and how it is managed in SIreview correspondence and/or equivalence strategies by neologism category.The latter part will discuss how the widespread use of neologisms should be reflected in the pedagogy of interpreters in order to ensure that they do not interpret the literal meaning but rather are faithful to the speaker’s meaning, in order to ensure intelligibility, thereby remaining competitive in this ever-changing interpretation market through clear and effective communication.